Materialnost branja - Vogrinčič, Ana (Primerjalna književnost, 2011)
Despite the physical materiality of books and reading often being neglected in the literary studies, the history of book practices repeatedly draws our attention to the significance of the non-textual aspects of the literary experience. In my contribution I will present various dimensions of the materiality of reading, which were already evident when novel reading became a popular and relatively wide-spread leisure practice, i.e., in 18th-century England. Using examples, notably the notorious bestselling Richardson's Pamela, I will try to show that novel reading could not emerge and proliferate without certain material dimensions of the novel and novel reading, or without the ways in which what was read was articulated, i.e., "externalised" through conversation, domestic performances of selected episodes, discussions in book clubs, societies and libraries, and in particular through re-enactment of fictional characters in other leisure and social activities. I will conclude by reflecting on contemporary versions of the "externalisation" of reading, and on the evidently increased interest for the materiality of books, which seems to be one of the side-effects of the recent metamorphosis of book formats.
Keywords: Richardson, Samuel, 1689-1761; "Pamela"; Literarne študije; zgodovina branja; angleška književnost; novel; roman; 18.st.; bralna kultura